Impact of Destination Image on Tourist Intention to Revisit Thru Satisfaction as an Intervening Variable at Eka Karya Botanical Garden, Bali - Ni Made Suwijati; I Nyoman Sudiarta; Yayu Indrawati (International journal of technology and education research, 2024)
Tourists choose destinations to visit based on the description of the destination. If visitors feel satisfied with the tourist spot, they will visit the destination again and will then provide recommendations to other people. Destination image is not only a destination attribute, but also the overall impression displayed by the destination. The Eka Karya Bali Botanical Gardens is a unique place on the island of Bali that combines botanical research, plant conservation, education, and recreation and has a good rating from tourists as proven by the results of reviews on Google Reviews, many tourists gave positive comments. However, apart from positive reviews, there are also many negative reviews from tourists who have visited the Eka Karya Bali Botanical Gardens due to the environmental conditions being poorly maintained and the prices being quite expensive. Based on this negative assessment, this research was carried out to see the truth about the Eka Karya Bali Botanical Gardens. This research aims to determine the image of the Eka Karya Bali Botanical Garden destination among tourists. The data collection technique in this research used a questionnaire, then the sample determination technique used accidental sampling, namely determining respondents based on anyone who was met by chance at the research location. The sample in question was tourists who visited the Eka Karya Bali Botanical Gardens, totaling 240 respondents. The data analysis technique used in this research is quantitative descriptive, then hypothesis testing using professional smart PLS 3.0 software. The results of this research conclude that destination image has a significant influence on satisfaction, satisfaction has a significant influence on intention to visit again, destination image has a significant influence on intention to visit again, satisfaction has a significant influence on intention to visit again, and destination image has a significant influence on intention to visit again. through tourist satisfaction.